2016
DOI: 10.1111/jvs.12467
|View full text |Cite
|
Sign up to set email alerts
|

Warming and nitrogen addition effects on bryophytes are species‐ and plant community‐specific on the eastern slope of the Tibetan Plateau

Abstract: Question Global change is likely to strongly affect alpine and sub‐alpine regions, in which bryophytes are important components. Global change effects on sub‐alpine vegetation, bryophytes in particular, however, have been addressed in few studies. We ask if global warming and increased nitrogen (N) deposition, two of the most important components of global change, will have different effects on bryophyte communities and species in sub‐alpine coniferous and shrubland ecosystems. Location Eastern slope of the Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 54 publications
4
3
0
Order By: Relevance
“…Negative responses of bryophytes to experimental warming have also been reported in previous experimental studies ( Elmendorf et al 2012a ; Lang et al 2012 ; Sistla et al 2013 ). Cover richness in the present study began to decline more markedly after 7 years of warming, as also found in other shorter-term studies in Sweden and Tibet ( Alatalo et al 2015a ; Sun et al 2017 ). However, bryophyte responses to long-term warming are not always negative ( Van Wijk et al 2003 ; Hudson and Henry 2010 ; Bokhorst et al 2016 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Negative responses of bryophytes to experimental warming have also been reported in previous experimental studies ( Elmendorf et al 2012a ; Lang et al 2012 ; Sistla et al 2013 ). Cover richness in the present study began to decline more markedly after 7 years of warming, as also found in other shorter-term studies in Sweden and Tibet ( Alatalo et al 2015a ; Sun et al 2017 ). However, bryophyte responses to long-term warming are not always negative ( Van Wijk et al 2003 ; Hudson and Henry 2010 ; Bokhorst et al 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…The response of bryophytes to climate warming may also be context-specific, depending on potential competition from vascular plants ( Molau and Alatalo 1998 ; Jägerbrand et al 2012 ) and the origin of the sampled population, as shown in an ex situ experiment in Japan ( Jägerbrand et al 2014 ). Moreover, most studies provide summaries of cover/biomass of whole bryophyte communities ( Sistla et al 2013 ), while only a few have collected species-level data to study the impact on species or bryophyte diversity and richness ( Molau and Alatalo 1998 ; Jägerbrand et al 2003 ; Wahren et al 2005 ; Klanderud 2008 ; Klanderud and Totland 2008 ; Lang et al 2012 ; Alatalo et al 2014a , 2015a ; Sun et al 2017 ). Climate change can also have indirect effects on bryophyte communities.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that bryophyte cover expansion was suppressed in response to experimental warming is in line with decreasing bryophyte abundance in several warming experiments from across alpine and arctic sites (Walker et al 2006;Elmendorf et al 2012aElmendorf et al , 2012bSistla et al 2013;Sun et al 2017) as well as previous findings of a short term (four years) study from the same site (Klanderud and Totland 2005). In contrast, experimental warming increased bryophyte cover in a High Arctic site (Hudson and Henry 2010;Edwards and Henry 2016) and increased moss cover and sexual reproduction in an Antarctic site (Casanova-Katny et al 2016;Shortlidge et al 2017;Prather et al 2019), indicating that rising temperatures could be beneficial for bryophytes under moist conditions or in the absence of competition from vascular plants.…”
Section: Discussionsupporting
confidence: 84%
“…The response of bryophytes to climate warming may also be context-specific, depending on potential competition from vascular plants (Molau and Alatalo 1998;Jägerbrand et al 2012) and the origin of the sampled population, as shown in an ex situ experiment in Japan (Jägerbrand et al 2014). Moreover, most studies provide summaries of cover/biomass of whole bryophyte communities (Sistla et al 2013), while only a few have collected species-level data to study the impact on species or bryophyte diversity and richness (Molau and Alatalo 1998;Jägerbrand et al 2003;Wahren et al 2005;Klanderud 2008;Klanderud and Totland 2008;Lang et al 2012;Alatalo et al 2014aAlatalo et al , 2015aSun et al 2017). Climate change can also have indirect effects on bryophyte communities.…”
Section: Introductionmentioning
confidence: 99%